Growth mindsets and psychological distress: A meta-analysis. (April 2020) - Burnette, Jeni L.; Knouse, Laura E.; Vavra, Dylan T.; O'Boyle, Ernest; Brooks, Milan A.
Abstract: We investigated if growth mindsets—the belief in the malleable nature of human attributes—are negatively related to psychological distress and if they are positively related to treatment value and active coping. In the meta-analysis, we included articles published between 1988 and 2019, written in English, that reported on mindsets as well as a qualifying dependent variable and included information required to calculate an effect size. With a random effects approach, meta-analytic results ( k = 72 samples, N = 17, 692) demonstrated that mindsets relate, albeit with minimal effects, to distress, treatment and coping. Specifically, there is a negative relation between growth mindsets and psychological distress ( r = −0.220), a positive relation between growth mindsets and treatment value ( r = 0.137) and a positive relation between growth mindsets and active coping ( r = 0.207). Differences in mindset domain, assessment method of mindsets and timing of assessments moderated effects. There were not differences based on operationalization of psychological distress outcome or sample characteristics (i.e., developmental stage, diagnostic status, ethnicity). We discuss theoretical and practical applications of the findings. Highlights: Results ( k = 72 samples; N = 17, 692) suggest a link between mindsets and mental-health outcomes. Growth mindsets are negatively related to psychological distress. Growth mindsets are positively related to treatment value and active coping. Domain and assessment of mindsets as well as assessment timing moderated effects. Effects did not differ based on psychological distress type or sample characteristics.